Patogenisitas Vibrio Fluvialis 24SK terhadap Kerapu Tikus (Cromileptes altivelis) - Indah Istiqomah; Alim Isnansetyo; Triyanto Triyanto; Kamiso Handoyo Nitimulyo; Muhammad Murdjani (Jurnal Perikanan Universitas Gadjah Mada, 2006)
This research was aimed to investigate the pathogenicity of Vibrio fluvialis 24SK in humpback grouper (Cromileptes altivelis) based on its Lethal Dosage 50 (LD50). V. fluvialis 24SK was isolated from ren of humpback grouper cultured in floating net cage at Brackishwater Aquaculture Development Center (BADC) Situbondo, with vibriosis signs. The bacterium was cultured in Tryptone Soy Broth (TSB) medium dissolved in trisalt solution (KCl, 0.75 g/l; MgSO4.7H2O; 14.2 g/l; NaCl, 18.4 g/l), incubated at 300C for 24 h. Infection was carried out by interperitoneal injection to humpback grouper (8-9 cm of total length) at 102, 104, 106, and 108 cfu/fish. Control fishes were injected with 0.2 ml trisalt solution. Disease sign and mortality of fishes were observed every eight hour for 40 days. LD50 was calculated based on Dragstedt Behrens method (Hubert, 1980). Result indicated that infection of the bacteria at 106 and 108 cfu/fish caused sub-acute disease signs, such as haemorhagic on operculum, base of fins (pinnae pectorales, pinnae abdominales, pinna analis), and also head and abdomen, while infection at 102 and 104 cfu/fish caused chronic disease signs, such as haemorhagic on fins base which was followed by necrotic on fins and skin tissue in prolonged time. Histopathologically, infection of the bacteria caused atrophy on the gills, infiltrations of lymphocyte, heterofel and plasma cell on the gills and fins base, vacuolar degeneration on the liver, and also present the bacteria colony on the fins base and intestine tissues. V. fluvialis 24SK has LD50 at (1,1±0,5)x107 cfu/fish.